Character Education Oriented Physics E-Module Development in the Static Fluid Section - Pratiwi Ineke Anwar; Abidin Pasaribu; Melly Ariska; Hamdi Akhsan (Universitas Lambung Mangkurat, 2021)
This development research aimed to produce a valid and practical character education-oriented Physics e-module for students Class XI Senior High School. The model used in this research was the development of Rowntree with three stages, namely the planning stage, the development stage, and the evaluation stage. At the evaluation stage, Tessmer's formative evaluation was used, namely, self-evaluation, expert review, one-to-one evaluation, small group evaluation to determine the validity and practicality of the e-module. The characteristics of the developed e-module were oriented in static fluid material on several character values, namely religious, curiosity, discipline, cooperation and communicativeness. The orientation aimed to instill the values of religious character, curiosity, discipline, cooperation and communicativeness in students. At the expert review stage, the average results of content, language, and design validation respectively were 4.5, 4.5 and 5 with very valid categories. In the one-to-one and small group evaluation stage, the average results of the assessment on the use of the developed e-module were 4.05 and 4.35 with practical and very practical categories. The implication of this research was that it can be used as one of the teaching materials used in learning also as a learning resource that aims to motivate students to learn independently.